2015
DOI: 10.1515/jppr-2015-0051
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity relationship study for fungicidal activity of 1-(4-phenoxymethyl-2-phenyl-[1,3]dioxolan-2-ylmethyl)-1H-1,2,4-triazole derivatives against rice blast

Abstract: Abstract:To explore new antifungal agents for rice blast control, the antifungal activity of a series of novel 1,2,4-triazole derivatives against Magnaporthe oryzae has been evaluated. The antifungal activity was determined by using in vitro mycelial growth inhibition tests. Among the 19 test compounds, we found that the compound 1-(4-phenoxymethyl-2-phenyl-[1,3]dioxolan-2-ylmethyl)-1H-1,2,4-triazole (Gj) displayed potent antifungal activity against M. oryzae. The IC 50 value was found approximately 3.8±0.5 μM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Thus, a large number of studies have been performed to isolate effective chemicals and metabolites. It was also reported that several chemicals including antibiotics can effectively prevent plant diseases caused by bacteria and fungi (Chand et al 1979;McManus et al 2002;Iwai et al 2007;Karthikeyan and Gnanamanickam 2011;Khan et al 2012;Hoshi et al 2015). Therefore, we inferred that human drugs can also have curative effects on plant diseases.…”
Section: Resultsmentioning
confidence: 60%
“…Thus, a large number of studies have been performed to isolate effective chemicals and metabolites. It was also reported that several chemicals including antibiotics can effectively prevent plant diseases caused by bacteria and fungi (Chand et al 1979;McManus et al 2002;Iwai et al 2007;Karthikeyan and Gnanamanickam 2011;Khan et al 2012;Hoshi et al 2015). Therefore, we inferred that human drugs can also have curative effects on plant diseases.…”
Section: Resultsmentioning
confidence: 60%
“…The effect of the chlorine atom on the various positions of the phenoxy moiety (ring B) such as 24a, 24b, and 24c can lead to an increase in antifungal activity. As a result, the fungicidal activity of the analogue without a chlorine substituent at ring B (24j) was the most effective against M. oryzae among these compounds ( Figure 22 ) [ 105 ].…”
Section: 124 Triazole Scaffold For the Development Of Antifungal Agentsmentioning
confidence: 99%
“…Moreover, the key enzymes in the biosynthesis of brassinosteroids have been evaluated to study their role against Magnaportheoryzae [causing rice blast disease]. It was found that the compound 2RS, 4RS-1-[4-chlorophenyl-(2-methylphenoxy)-ethyl]-1,3-dioxolan-2-yl-methyl]-1H-1,2,4-triazole was a potent antifungal agent against Magnaportheoryzae [113]. Another study reported by Kim et al [114] found that 24-epibrassinolide (EBL) reduced Fusarium wilt in cucumber and enhanced their antioxidant and phenolic levels in roots.…”
Section: Antifungal and Antibacterial Activitiesmentioning
confidence: 99%